Ab Interno Canaloplasty in Open-angle Glaucoma Patients Combined With In Vivo Trypan Blue Aqueous Venography. Issue 12 (December 2020) - Docherty, Gavin; Waldner, Derek; Schlenker, Matt; Crichton, Andrew; Ford, Bryce; Ahmed, Iqbal I.K.; Gooi, Patrick
Abstract : Purpose: To demonstrate canalogram patterns observed when trypan blue tracer is combined with oculoviscoelastic device during ab interno canaloplasty, and discuss surgical results and potential implications for diagnosis, prognosis, and treatment. Methods: This is a retrospective small case series study. Results: The authors performed this procedure on 5 patients with informed consent with 4 to 18 months of follow-up. All procedures have been complication free. The average preoperative intraocular pressure was 16.4 mm Hg with an average number of topical glaucoma medications being equal to 3.6. Postoperatively, the average intraocular pressure for the group was reduced to 13 mm Hg with a concurrent drop in the average number of topical medications used equaling 1.8. Conclusions: Currently, there are limited practical options to evaluate the patency of the aqueous outflow system in our patients. The primary purpose of this paper is to describe canalogram patterns observed during ab interno canaloplasty with trypan blue. This technique may allow us to further our understanding of the aqueous outflow system and its role in the underlying pathophysiology of glaucoma. Further research is required to evaluate the prognostic and diagnostic significance of this technique.